THE EFFECTIVENESS OF USING ALEF EDUCATION MEDIA TO ENHANCE VOCABULARY MASTERY - Muttaqiyyah, Almar'atul (Kitaba, 2024)
This research discusses the effectiveness of implementing the "Alef Education" media, which contains interesting digital-based features for Arabic language learning, to improve vocabulary mastery as a case study in the 7th grade of MTsN 1 Kediri. The academic problems identified by the researcher include: 1) Lack of Arabic vocabulary repertoire among students, 2) Lack of student interest in learning vocabulary using books, 3) Students' difficulty in memorizing vocabulary. The objectives of this research are: 1) to determine the process of implementing Alef Education media, 2) to assess the effectiveness of implementing Alef Education media, 3) to identify the strengths and weaknesses of implementing Alef Education media. The research methodology used is a mixed-methods research combining quantitative true-experimental design and qualitative approaches. The data collection methods include pre-tests and post-tests, questionnaires, interviews, documentation, as well as relevant and supportive literature. The research results indicate that: 1) The process of implementing Alef Education media includes opening, core, and closing activities. 2) There is a significant improvement in students' vocabulary mastery, which is proven effective through SPSS calculations using the Independent Sample t-Test, with a 2-tailed significance value of 0,02 0,05, thus rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). 3) The advantages of implementing Alef Education media include engaging and easily understandable learning, the presence of exercise questions accompanied by images and audio that motivate students in memorizing and improving learning outcomes. However, the disadvantages include technical issues and reduced use of books.